Cation‐Selective Oxide Semiconductor Mesoporous Membranes for Biomimetic Ion Rectification and Light‐Powered Ion Pumping. Issue 35 (5th August 2022) - Li, Li; Sun, Mingyan; Hu, Ziying; Nie, Xiaoyan; Xiao, Tianliang; Liu, Zhaoyue
Abstract: Artificial membranes precisely imitating the biological functions of ion channels and ion pumps have attracted significant attention to explore nanofluidic energy conversion. Herein, inspired by the cyclic ion transport for the photosynthesis in purple bacteria, a bilayer inorganic membrane (TiO2 /AAO) composed of oxide semiconductor (TiO2 ) mesopores on anodic alumina (AAO) macropores is we developed. This inorganic membrane achieves the functions of ion channels and ion pumps, including the ion rectification and light‐powered ion pumping. The asymmetric charge distribution across the bilayer membrane contributes to the cationic selectivity and ion rectification characteristics. The electrons induced by ultraviolet irradiation introduce a built‐in electric field across TiO2 /AAO membrane, which pumps the active ion transport from a low to a high concentration. This work integrates the functions of biological ion channels and ion pumps within an artificial membrane for the first time, which paves the way to explore multifunctional membranes analogous to its biological counterpart. Abstract : A cation‐selective bilayer inorganic membrane composed of oxide semiconductor mesopores on anodic alumina macropores integrates the functions of biological ion channels and ion pumps in purple bacteria. The asymmetric charge distribution across the membrane contributes to the ion rectification. The light‐induced built‐in electric field pumps the uphill ion transport.